Upaya Pembentukan Kedisiplinan melalui Pembiasaan Shalat Berjama’ah di TPQ & Madrasah Diniyah Thoriqul Jannah Annahdliyah Purwosari - Al-amri, Thol'atul Luthfi; Aziz Q, Ikhwan; Arifin, M. Zainal (Jurnal Keislaman, 2024)
Religious education given to children from an early age aims to increase religious potential and develop the child's personality through prayer so that from an early age the child becomes a person who believes and is devoted to Allah. Al-Qur'an Learning Center & Madrasah Diniyah Thoriqul Jannah Annahdliyah are non-formal educational institutions that not only prioritize religious education for children but also attitudes towards children. There are still students who lack discipline, so it is necessary to instill a disciplined attitude through the habit of praying together. With the identification of problems in this research, namely: There is still a lack of time discipline among students, there are still students who violate discipline. And the focus of the problem is: Implementation of congregational Asar prayer activities for Al-Qur'an Learning Center & Madrasah Diniyah Annahdliyah Thoriqul Jannah students as an effort to form student discipline. The aim of this research is to understand how the process of getting used to congregational prayer is carried out by ustadz/ustadzah to form student discipline. This research uses qualitative field research methods. With a case study approach. The conclusion of this research is that the habit of congregational prayer is effective as a breakthrough in efforts to form discipline in students.